2019
DOI: 10.1111/jcmm.14873
|View full text |Cite|
|
Sign up to set email alerts
|

Platelet sonicates activate hair follicle stem cells and mediate enhanced hair follicle regeneration

Abstract: An increasing number of studies show that platelet-rich plasma (PRP) is effective for androgenic alopecia (AGA). However, the underlying cellular and molecular mechanisms along with its effect on hair follicle stem cells are poorly understood. In this study, we designed to induce platelets in PRP to release factors by calcium chloride (PC) or by sonication where platelet lysates (PS) or the supernatants of platelet lysate (PSS) were used to evaluate their effect on the hair follicle activation and regeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…These molecules included growth factors, cytokines, and ECM molecules, and many of them potentially activated PI3K/ Akt pathway [18,19]. This is consistent with recent findings that platelets and mesenchymal stem cells (MSCs) promote wound healing and hair regrowth through paracrine factors, which potentially induce activation of PI3K/Akt pathway in effector cells [33][34][35][36]. Platelets are the first cell type to arrive at the site of tissue injury, where they play diverse roles through the release of various bioactive molecules [37].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These molecules included growth factors, cytokines, and ECM molecules, and many of them potentially activated PI3K/ Akt pathway [18,19]. This is consistent with recent findings that platelets and mesenchymal stem cells (MSCs) promote wound healing and hair regrowth through paracrine factors, which potentially induce activation of PI3K/Akt pathway in effector cells [33][34][35][36]. Platelets are the first cell type to arrive at the site of tissue injury, where they play diverse roles through the release of various bioactive molecules [37].…”
Section: Discussionsupporting
confidence: 84%
“…These studies imply an effect of PRP on hair follicle stem cells, which are key effector cells for hair follicle growth. Indeed, in our recent study, we found that PRP, which contained various growth factors, activated quiescent hair follicle stem cells to proliferate, resulting in the transition of telogen (resting phase) to anagen (growing phase) hair follicles in mice [35]. In line with these observations, recent studies showed that transplantation of autologous cells prepared from the hair follicle could form de novo hair follicles in AGA patients [53,54].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Damage to or the absence of skin appendages not only delays wound healing but also leads to incomplete skin function and scar outcomes [ 43 ]. There have been clinical cases of PRP used in the treatment of alopecia [ 44 , 45 ], and further in-depth research found that it could affect the hair growth cycle and is beneficial to hair follicle reconstruction [ 46 , 47 ]. Interestingly, the hair follicles and sebaceous glands were distributed in the newborn skin in the PRP group on day 14, which is consistent with previous research.…”
Section: Discussionmentioning
confidence: 99%
“…For adipose-derived research [44][45][46], the components that are typically used for aesthetic and dermal applications consist of nanofat, stromal vascular fraction cells (SVFs), adipose-derived mesenchymal stem cells (AD-MSCs), and extracellular vesicle (EVs), which have all shown capability to repair, regenerate, and rejuvenate surrounding tissue. For blood-derived research [47][48][49][50][51], studies focused on platelet-rich plasma (PRP), which is a whole-blood centrifuged concentrate that contains proteins and growth factors (GFs) but not red blood cells. However, although many papers on PRP have been published, the results are often contradictory.…”
Section: Discussionmentioning
confidence: 99%